Kalendarium - Ulicka, Danuta (Przestrzenie Teorii, 2008)
The listing of the dates of life and work of Mikhail Mikhailovich Bakhtin and of the leading members of his philosophical-literary clubs has been compiled based on the available data, sometimes still uncertain ones. Admittedly, a list of dry facts will not replace a monograph which does not exist in Poland, however, it allows at least to order the most important facts, biographical and editorial facts around which a lot of misunderstanding, conjectures and false convictions have grown. Like each such chronology it is selective and in agreement with the author's cognition of the whole and its interpretation. However, it does not impose them, leaving to the readers the liberty of creating their own narrations. As opposed to similar English and Russian chronologies (calendars), it introduces figures who are considered to be of second-rate (Nikolai Bakhtin, Konstantin Vaginov, Boris Zubakin, Mikhail Tubiansky) - probably only due to the fact that their works are still less known than those of the main heroes. Meanwhile it is they who give the idea about the impetus and variety of this strange unofficial and antiofficial institution which were Bakhtin's circles.